SÍNTESE E CARACTERIZAÇÃO DE NANOTUBOS AUTO-DOPADOS DE TIO2-X E SUA APLICAÇÃO NA DEGRADAÇÃO FOTOELETROCATALÍTICA DO CLORIDRATO DE PROPRANOLOL - OLIVEIRA, ELIZANDRA MAIARA DE (2022)
Heterogeneous photocatalysis is an alternative treatment technique for drug degradation, as it is a green technology, capable of mineralizing numerous species of pollutants. Therefore, the influence of the morphological and microstructural properties of electrochemically reduced TiO2 films was investigated on the mineralization of the drug propranolol hydrochloride. The films were synthesized through the technique of potentiostatic anodization in different organo-aqueous solutions, and the influence of the presence of simulated body fluid (SBF) in the solution was studied. The images obtained by SEM revealed that the presence of SBF in the solution reduces the dissolution rate of the oxide, resulting in a nanoporous morphology. Furthermore, for the sample synthesized in the absence of SBF and subjected to -1.4 V reduction, this potential resulted in the collapse of the nanotubular structure to nanospongy, indicating that the lack of SBF reduces the mechanical stability of the samples. The X-ray diffraction patterns revealed that the electrochemical reductions in the negative potentials of -1.0 and -1.2 V, for both electrolyte solutions investigated, were effective for the formation of Ti3+ ions in the TiO2 nanotube arrays. Electrochemical characterization showed that films reduced at -1.4 V had increased photocurrent responses, in which the presence of SBF resulted in a photocurrent ~2.2 times higher than the film synthesized in the absence of SBF and subjected to the same reduction potential. From the bandgap, it was observed that the samples submitted to the potential of -1.2 V presented a reduction of the bandgap in relation to the other films. From the degradation tests, the methodology used that resulted in a better performance was photoelectrocatalysis with photocatalysts reduced to a potential of -1.2 V and, among them, the presence of SBF favored the efficiency of the process. In this way, it was possible to conclude that the variables studied influenced the responses obtained, which highlights the importance of searching for efficient methodologies of degradation for application in the industrial scope.